PARADIGMA DIALEKTIKA PADA AKUNTANSI LINGKUNGAN - Natalia, Irene; Situmorang, Bornok; Hastutie Noor Andriati; Sanggenafa, Mariolin A.; Atmadja, Soesilawati Soema (Fortunate Business Review, 2025)
This article aims to explore a deeper understanding of the phenomenon of dualism of opinion on the existence of environmental accounting. This study examines environmental accounting from the perspective of Hegel. This study proposes a new approach that accommodates both thesis and antithesis, ultimately leading to a synthesis. This study conducts a review and examination of various documents, including books, research results, laws and regulations, and other electronic sources. The study is presented together with the author's critical opinion, which is conceptualised so that this study is a conceptual paper. The study's results begin with the differences in approach between those who accept and those who reject environmental accounting, along with their respective arguments (thesis and antithesis). In the end, the author presents a critical opinion (conceptual) in the form of a synthesis, arguing that regulations are needed to accommodate environmental accounting, so that stakeholders can avoid behaviour that has the potential to cause damage to the ecosystem.